Estimation of serum minerals and glucose following subcutaneous melatonin treatment for restoration of ovarian cyclicity in summer anestrus buffaloes (Bubalus bubalis) - KUMAR, ASHOK; MEHROTRA, S; SINGH, G; KHATI, AMIT; KADIRVEL, G; MAHLA, A S; JAIN, SHASHANK; PATEL, A K (The Indian Journal of Animal Sciences, 2019)
The present investigation was designed to uncover the effect of melatonin on serum calcium, phosphorus and glucose concentration following restoration of ovarian cyclicity in summer anestrus buffalo. The investigation was conducted on 28 healthy postpartum Murrah buffalo cows of age 5.11Â±0.62 years having body weight of 539Â±17.48 kg maintained under isomanagerial conditions with intensive system. Buffaloes diagnosed as summer anestrus (28) on the basis of absence of estrus signs three months postpartum, absence of ovarian activity by rectal examination and serum progesterone assay at 10 days interval. Buffaloes were grouped as untreated (Group I, sterilized corn oil, 8) and treated (Group II, single S/C injection of melatonin (MLT) @18 mg/50 kg b.wt in sterilized corn oil, 20). Estrus detection was carried out twice daily using teaser bull parading along with observation of behavioural estrus signs till day 28 post-treatment. Blood samples were collected at 4-day interval starting from day 8 pretreatment to 28 day post-treatment and for the entire cycle length in responded animals at 4-day interval. Serum calcium, phosphorus and glucose were estimated by commercial kits. Serum Ca, P and glucose concentrations in MLT treated and control buffaloes did not differ significantly within and between both groups. Serum Ca, P and glucose concentrations did not alter significantly between days of MLT induced estrous cycle. However, the group and period effect as well as interaction effect of group and period in serum calcium and phosphorous were not significant whereas, the group and period effect was significant but interaction effect of group and period were not significant in serum glucose concentration. Estrus induction rate was 90% with overall conception rate of 32.4%. Hence, it may be concluded that MLT supplementation restored cyclicity resulting in improvement in conception rate without significantly altering serum calcium, phosphorous and glucose concentration in summer anestrus buffaloes.